Low Compression in the Cylinder of Aircraft Piston Engine Due to Gas Leakage - Ego Widoro; Bhima Sakti Arrafat; Ryan Okta Ramadhani; Renaldi Rizki Purba (Politeknik Penerbangan Indonesia Curug, 2025)
Piston-prop aircraft are typically used in general aviation and consist of an internal combustion engine paired with a propeller. The combustion chamber in the cylinder must remain leak-proof during the compression and power strokes to maximize power output. Leakage in the combustion chamber is one of the factors that cause failure to reach peak pressure during the compression stroke. This study focuses on low compression in the cylinder of the aircraft piston engine due to gas leakage, failing to reach peak pressure. Three experienced aircraft maintenance engineer license holders were involved in the interview for this study. Most frequently occur in valves, particularly in exhaust valves due to carbon deposits accumulating around the valve face. Second, piston leaks are indicated by too large side clearance of compression piston rings or in-line compression piston ring gaps, and finally, although leaks are rarely found in the spark plug area, it is still recommended to check this area when performing a compression check. Further research can be conducted using quantitative research to determine the frequency of occurrence. It can also be done with intensive research involving laboratories to find out the cause.